Estudios radiológicos en el diagnostico de plastrón apendicular - Farías Pérez, Ginger Lizbeth (Machala : Universidad Técnica de Machala, 2021)
INTRODUCTION: The appendicular plastron is a palpable inflammatory mass in the abdominal region at the level of the right iliac fossa, it indicates a peritoneal reaction located around the inflamed appendix that is generally in its last perforation phase. It usually originates after an inflammatory process of the appendix, it is an acute condition that begins due to obstruction of the appendicular lumen, mostly due to hypertrophy of lymphoid follicles and can cause a perforation that progresses to the presence of a mass. OBJECTIVE: To determine the radiological studies in the diagnosis of appendicular plastron, by means of the bibliographic review of scientific articles. METHODS AND MATERIALS: A descriptive study was carried out through the review of scientific articles that provide essential information for the correct diagnosis, which was fulfilled with the systematic search for scientific information such as COCHRAINE, PUB-MED, GOOGLE ACADEMIC of the last 5 years. CONCLUSION: For a correct diagnosis of appendicular plastron, it is important to consider an ultrasound as an initial complementary examination, and subsequently a mandatory computed tomography should be requested, in which radiological findings are observed identifying the mass with surrounding fat trabeculation and location of fat and grouping of the loops in the right iliac fossa, in addition, associated lymphadenopathy can be evidenced.
INTRODUCCIÓN: El plastrón apendicular es una masa inflamatoria palpable en región abdominal a nivel de fosa iliaca derecha, indica una reacción peritoneal localizada alrededor del apéndice inflamada que generalmente se encuentra en su última fase de perforación. Se origina por lo general después de un proceso inflamatorio del apéndice, es un cuadro agudo que se inicia por obstrucción de la luz apendicular, en su mayoría por hipertrofia de folículos linfoides y puede provocar una perforación que progresa a la presencia de una masa. OBJETIVO: Determinar los estudios radiológicos en el diagnóstico de plastrón apendicular, por medio de la revisión bibliográfica de artículos científicos. MÉTODOS Y MATERIALES: Se procedió al estudio descriptivo por medio de la revisión de artículos científicos que faciliten información indispensable para el diagnóstico correcto, el cual se cumplió con la búsqueda sistemática de información científica como, COCHRAINE, PUB-MED, GOOGLE ACADEMIC de los últimos 5 años. CONCLUSIÓN: Para un correcto diagnóstico de plastrón apendicular, es importante considerar una ecografía como un examen complementario inicial, y posteriormente se debe solicitar una tomografía computarizada obligatoria, en la cual se observa hallazgos radiológicos identificando la masa con trabeculación de grasa circundante y localización de grasa y agrupamiento de las asas en fosa iliaca derecha, además, se puede llegar a evidenciar adenopatías asociadas.
Keywords: PLASTRON APENDICULAR; APENDICITIS; MASA APENDICULAR